PPAT Responsibility Due To Deed Cancellation - Fitriandi, Fitriandi; Suryono, Arief; Purwadi, Hari (CV. Inara, 2024)
Based on the background explained above, the problem formulation can be taken as follows what is the PPAT's responsibility for the cancellation of the PPAT sale and purchase deed with the right to repurchase and What are the responsibilities of the PPAT according to the Judge's considerations as a result of the cancellation of the sale and purchase deed with the right to repurchase in Decision Number: 100/PDT.G/2020/PN.KRG?. This research is a type of doctrinal research or also called normative legal research. Normative research is research carried out by reviewing legislation, court decisions, legal theory, and can be in the form of opinions of scholars which are compiled systematically and then draw conclusions in relation to the problem being studied. The results of this research are repurchase rights in transactions between Darwanto and SN. Joko Mursito, as proven by the Deed of Sale and Purchase Number 640/287/MTS/2020, which was then continued with a lawsuit to the court, according to the author, that in reality the sale and purchase with the right to repurchase was a pseudo sale and purchase because what occurred was a debt and receivable. Based on the Decision of the Supreme Court of the Republic of Indonesia Number 1729 PK/Pdt/2004 concerning buying and selling with the right to repurchase, the right to repurchase as regulated in Article 1519 of the Civil Code is not permitted. Cancellation of a Notary/PPAT deed through a court decision is not only due to errors or negligence of the Notary/PPAT in making the deed. However, the cancellation of a Notarial/PPAT deed can also be caused by errors or negligence of the parties who bound each other in the deed.